Dose‐dependent induction of signaling pathways by the flavonoid quercetin in human primary hepatocytes: A transcriptomic study. Issue 6 (5th May 2015) - Waizenegger, Julia; Lenze, Dido; Luckert, Claudia; Seidel, Albrecht; Lampen, Alfonso; Hessel, Stefanie
<x xml:space="preserve">Abstract</x> Scope Quercetin is widespread in plant kingdom and consumed regularly with human diet (16 mg/day). Due to reported positive effects on health, quercetin supplements with recommended doses up to 2 g/day are offered. However, molecular effects of such high doses on human liver have not been assessed yet. Therefore, molecular effects on human hepatocytes were analyzed to help assessing the risk of quercetin supplementation. Methods and results Molecular effects of three different quercetin concentrations on gene expression in human hepatocytes were investigated by microarray analysis. Possible new signaling pathways were investigated using reporter gene assays. Quercetin concentrations representing the normal intake showed weak effects on mRNA expression in liver cells. In contrast, supplemental doses affect immune response and p53 signaling and might be associated with cancer. Additionally, quercetin showed inhibition of transcriptional activation and mRNA‐expression of HNF4α and its target genes. Inhibitory effects were also found for FXR, LXRα, and PXR. Conclusion Normal intake of quercetin seems to play a minor regulatory role, while supplement doses may have great effects on gene expression in hepatocytes. However, since it is not clarified whether such high doses of quercetin exert positive or negative effects, a careful handling of quercetin supplements is advised.